(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study explores the impact of social media marketing on small businesses in the municipality of Santa Cruz, focusing on branding, customer relationships, and pricing. Using a descriptive survey method, the researchers gathered data from selected small business owners in various barangays, including Banahaw, Maharlika, Bagong Silang, Lapu Lapu, and Pagasa. The findings reveal that social media marketing significantly boosts revenue for small businesses, enhances customer education, and facilitates effective communication. However, respondents also face challenges in branding, such as establishing a recognizable presence, handling negative feedback, and competing with larger enterprises.